ALGORITHM DEVELOPMENT FOR ASSESSMENT OF ACCURACY POSITIONING SYSTEMS GLONASS/GPS WITH DIFFERENTIATED APPLICATION OF FERTILIZERS - G. I. Lichman; V. A. Kolesnikova; N. M. Marchenko; A. N. Marchenko (Сельскохозяйственные машины и технологии, 2017)
One of the directions of increase in fertilizers efficiency is reduction of nonuniformity of their distribution across the field. Quality of fertilizer application decreases in particular because of diagram joining violation when distributions at adjacent passes of units. The authors detected dependence of size of diagrams overlapping at adjacent passes of machines for surface fertilization on quality of distribution across the field. Analytical researches define dependence of a dose of fertilizers application on the unit driving accuracy characterized by variation coefficient. Received mathematical model make it possible to determine admissions on overlapping of adjacent passages at the corresponding mean square deviation from optimum. These deviations limits depend on the set dose of application, limit of a deviation from it, the accuracy of driving characterized by a square deviation of overlapping and average value of a deviation from overlapping to optimum and also on the empirical coefficients characterizing a diagram of distribution of fertilizers on the general operating width. With reduction of a square deviation the limits of a unit deviation from the set operating width increase and reach a maximum when value of this deviation is equal to zero. The authors offered an algorithm of assessment of influence of size of diagram overlapping at adjacent passes of machines for application of fertilizers on quality of distribution across the field. Methodical approaches to justification of requirements to the precision positioning systems GLONASS/GPS were formulated.